2020
DOI: 10.1103/physrevlett.124.161102
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Bound State Formation of Dark Matter in the Early Universe

Abstract: The thermal decoupling description of dark matter (DM) and co-annihilating partners is reconsidered. If DM is realized at around the TeV-mass region or above, even the heaviest electroweak force carriers could act as long-range forces, leading to the existence of meta-stable DM bound states. The formation and subsequent decay of the latter further deplete the relic density during the freeze-out process on top of the Sommerfeld enhancement, allowing for larger DM masses. While so far the bound-state formation w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 86 publications
(101 reference statements)
0
52
0
Order By: Relevance
“…So far, the formation of dark matter bound states via the emission of an on-shell mediator was considered as the dominant process. However, it was pointed out recently that this does not necessarily have to be the dominant BSF channel during the thermal dark matter freeze-out [63]. The conversion between scattering and bound states in the radiation dominated epoch can also efficiently take place via bath-particle scattering, where a mediator is exchanged virtually between a DM two-body pair and a relativistic primordial plasma particle.…”
Section: Jhep09(2020)086mentioning
confidence: 99%
See 2 more Smart Citations
“…So far, the formation of dark matter bound states via the emission of an on-shell mediator was considered as the dominant process. However, it was pointed out recently that this does not necessarily have to be the dominant BSF channel during the thermal dark matter freeze-out [63]. The conversion between scattering and bound states in the radiation dominated epoch can also efficiently take place via bath-particle scattering, where a mediator is exchanged virtually between a DM two-body pair and a relativistic primordial plasma particle.…”
Section: Jhep09(2020)086mentioning
confidence: 99%
“…While in ref. [63], a mediator with a mass larger than the binding energy was investigated, we consider massless or lighter mediators in the present work. The masses of SM force-carries is temperature dependent during the electroweak cross over, which motivates to investigate these cases more carefully.…”
Section: Jhep09(2020)086mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, our results can be recast to compute BSF via scattering on a bath of relativistic particles, through exchange of a charged scalar, according to the recent analysis of ref. [24]. This can be particularly important for the chemical decoupling of multi-TeV WIMP DM coupled to the 125 GeV Higgs [35]; in this regime the Higgs can indeed act as a light mediator [1,2], even if its on-shell emission in capture processes is not kinematically allowed.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [24] found that the rate of capture via scattering factorises into the radiative crosssection (albeit without any phase-space suppression due to the mass of the emitted scalar), times a part that includes the kinematics and dynamics of the bath particles. The cross-sections (2.25) can then be recast to calculate BSF via off-shell exchange of a charged scalar.…”
Section: Capture Via Scatteringmentioning
confidence: 99%